A Patient with Granulomatosus with Polyangiitis (Wegener’s Granulomatosis): A Case Report: A Case Report - Harris Hardian; Pande Ketut Kurniari; Gede Kambayana (Indonesian Rheumatology Association, 2023)
Background: Granulomatosus with Polyangiitis (GPA) is an Anti-neutrophilic Cytoplasmic Antibodies (ANCA) Associated Vasculitis (AAV) which involves small to moderate-sized vessels. GPA has a variety of clinical manifestations caused by tissue ischemia and organ affected. Diagnosis of GPA remains challenging, and its actual incidence may be higher than reported. In 1990, the American College of Rheumatology (ACR) published diagnostic criteria for GPA. Guidelines of management of GPA has improved survival in last decade, but results remain unsatisfactory. Induction agents with immunosuppressive agents and glucocorticoid, and the newer agent Rituximab are recommended as first choice treatment. Case presentation: A 64-year-old male presented with current episode of joint pain and a history of recurrent respiratory tract infections. After a series of laboratory and radiologic examinations, lung biopsy was performed, and the result was suggestive of GPA. The patient was managed with induction remission agent and reported improvement in both clinical and laboratory parameters. Conclusion: Granulomatosus with Polyangiitis is a limitedly reported case. This report was presented to raise awareness of the diagnosis when faced with similar clinical symptoms. Early detection and diagnosis in GPA allow for prompt and better management with the target to achieve and maintain remission, as demonstrated in this case.